Electrochemical degradation of aqueous alachlor and atrazine: products identification, lipophilicity, and ecotoxicity - Furtado, Rafaely Ximenes de Sousa; Azevedo, Eduardo Bessa; Motheo, Artur de Jesus (Eclética Química, 2019)
This work studied the electrochemical degradation of alachlor and atrazine (alone and mixed with each other) using a filter-press cell, a dimensionally stable anode (DSA Ti/Ru0.3Ti0.7O2), initial pH 3.0, and temperature at 25 °C. The best operational conditions for alachlor (0.33 mmol L-1) degradation were obtained by a 32 factorial design, in which the factors/levels were: NaCl concentration (0.05, 0.1, and 0.15 mol L-1) and current density (10, 30, and 50 mA cm-2). Thus, 93.1% alachlor removal and 71.2% mineralization were achieved using 0.15 mol L-1 NaCl and 30 mA cm-2. In addition, the initial degradation products (DPs) of alachlor and atrazine were identified by liquid chromatography coupled to mass spectrometry (LC-MS). Acute and chronic ecotoxicities for three trophic levels (fishes, daphnids and green algae) and lipophilicity (log D, pH 7.4) of the DPs were also estimated using the ECOSAR 1.11 and ChemAxon Calculator software, respectively. The present study showed that the electrochemical degradation is an efficient method for removing the herbicides alachlor and atrazine from water and that the DPs formed have lower pollution potential than their original compounds.